(3ahGFO aj eYQaI GdYed HfUa OGFQI GdeYOds
(3ChdgG (B:s
(3HYO GdHSedI hGdMeO dI hHYO agPg ahGFO aj eYQaI GdYed HfUa OGFQI GdeYOd GdaGFOI GdChdj s
(3BNQgG (B:s
(3agPg eWGdY GdQhM hEPG CQOJ eWGdY cd OQLI aGbSe eWGdYI Ydi YOO QLJg jMUd eGdNU cd OQLI s
(3Vef eLehY , JQJjHgG (B: 10s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJM (B(5308) s
Keywords: (3eJaQbGJs